ASYNCHRONOUS CASCADES - Karimov, Ne’matulla Ubaydulla o‘g‘li (Educational Research in Universal Sciences, 2023)
This article provides information on the use of additional motors to improve the driving performance of asynchronous motors commonly used in industry.